Construction Research Congress 2018 2018
DOI: 10.1061/9780784481271.067
|View full text |Cite
|
Sign up to set email alerts
|

Cost Management Practice of Construction Firms and Its Influencing Factors: Lessons from Southwestern Nigeria

Abstract: The growing need at maintaining steady cost projection of construction projects has been an issue of serious concern to both the clients and the construction practitioners on sites. Also, cost deviation from initial cost plan and cost budget has been prevalent on construction sites and no concerted efforts have been made at addressing this phenomenon. This study therefore examined the factors that are considered to be affecting the cost management practice of construction firms in the southwestern Nigeria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The decision rule for the hypothesis one with reference to Table 4 indicates there is no significant difference in the mean of the three methods, it then means that there is agreement in the opinions of the practitioners that the tendering method have uniformly resulted to the selection of incompetent contractors as shown in the summary calculations of Table 5. This is in accordance with Fagbenle et. al (2018) and Hansen (2021) views.…”
Section: Discussion Of Analysed Datasupporting
confidence: 94%
“…The decision rule for the hypothesis one with reference to Table 4 indicates there is no significant difference in the mean of the three methods, it then means that there is agreement in the opinions of the practitioners that the tendering method have uniformly resulted to the selection of incompetent contractors as shown in the summary calculations of Table 5. This is in accordance with Fagbenle et. al (2018) and Hansen (2021) views.…”
Section: Discussion Of Analysed Datasupporting
confidence: 94%
“…Cost management is one of the fundamental criteria of success in construction projects, thus it should be managed and control along the lifecycle of the project, the study focused on evaluation of cost management practices in large construction project in south Malaysia, the results indicated the most effective cost management techniques were: Cash Flow Forecasting, Tender Budgeting/Estimating and Elemental Cost Plan [17]. The most important factors that affected in cost management of construction projects in South-western Nigeria were: poor leadership and inappropriate management, inefficient deployment of resources, excessive wastage of materials on sites, complex payment mechanisms, theft of materials on sites and variation during construction works [18].…”
Section: Factors Affecting In Cost Managementmentioning
confidence: 99%
“…The experience and competence of the project manager were identified by (Al-Juwairah, 1997; Divakar and Jebin, 2018; Kissi et al, 2016) as a critical factor influencing cost management practices. Poor leadership and management were also highlighted by Fagbenle et al (2018) as being among the vital factors influencing the success of cost management. Where there is no will by top management to support efforts target at strategically positioning the company, the order will be wastage, high expenses and under usage of resources.…”
Section: Factors Influencing Cost Managementmentioning
confidence: 99%
“…This is despite that construction stakeholders know how important project cost is, and the impact it has when properly managed. Fagbenle et al (2018) suggested that a cost management study be carried out in other regions of Nigeria. There are few studies on cost management of construction projects in a developing country like Nigeria than in developed nations of the world.…”
Section: Introductionmentioning
confidence: 99%